POLIGAMI DALAM SOROTAN (Kajian Kitab-kitab Tafsir Modern/Kontemporer) - B, Halimah (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2020)
This study aims to analyze the views of modern/contemporary commentators on polygamy verses. This research is a descriptive qualitative research library (mawdu’i method) with the interpretation approach. The results of this study show that pro-contradictory polygamy is between those who oppose vigorously and those who allow it with strict requirements, that is if the husband can be fair to his wives. The group that allows them to base their views on QS al-Nisa ’4: 3. by setting some requirements; if the number of women who are eligible to marry more than men who are married, if the productive age of men has a grace period that is far from the productive age of women if the wife is infertile while the husband wants to have offspring, men have a strong libido ( super sex) unable to stem his lust if only one wife. Although these requirements are met, the basic requirements are not met then polygamy is prohibited. While those who oppose them strongly base their views on QS.al-Nisa ’/ 4: 129. that no one can be fair to wives, both fair treatment of problems related to the material and nonmaterial in the matter of love and affection.